The Plot of A. P. Chekhov’s “Liturgical Journey” in The Steppe - Galina V. Mosaleva (Два века русской классики)
The article examines A. P. Chekhov’s story The Steppe as a program work, a kind of dialogue with the steppe literary tradition rooted in ancient Russian literature, and at the same time as Chekhov’s new word about the Russian steppe. The lyricism and poetry of the work are interpreted in connection with its sacred, ontological nature. The four-day journey consists in the structure of the weekly service, from Saturday to Saturday. All the events and paths of the characters are built around the incessant liturgy. Chekhov’s existential symbols of steppe space are bell towers, mounds, crosses, and chapels. Chekhov’s natural and mythological world is sanctified and transformed under the influence of the temple space and the liturgical word. The article substantiates Chekhov’s understanding of the Steppe as an ontological metaphor of the Russian universe. During the journey, the little hero Egorushka grows up and matures, he learns to fight. A young hero growing up in the steppe learns to fight evil and its natural properties, such as longing, anger, isolation, signs of the apostasic world. Happiness, as Chekhov understands him, is the coincidence of his will with the will of God about himself, joyful sacrifice for the good of his neighbor, and the fulfillment of the divine program.